Crisis Management in Dakwah: A Critical Review of Islamic Legal Strategies During the Christian Conquest of North West Iberia Africa - Carimo Mohomed (Fakultas Dakwah UIN KHAS Jember, 2026)
The fall of Islamic rule in Iberia and North Africa presented a monumental crisis for the Muslim community, requiring strategic management to preserve faith and social cohesion under Christian occupation. This study aims to critically review Islamic legal strategies specifically fatwas as instruments of crisis management in dakwah during the Christian conquest of North West Africa and Iberia. This research employs a qualitative historical approach and literature review, critically analyzing the primary arguments and historical contexts presented in Jocelyn Hendrickson's